Enhanced N‐Type Doping of a Naphthalene Diimide Based Copolymer by Modification of the Donor Unit. (8th August 2021) - Cassinelli, Marco; Cimò, Simone; Biskup, Till; Jiao, Xuechen; Luzio, Alessandro; McNeill, Christopher R.; Noh, Yong‐Young; Kim, Yun‐Hi; Bertarelli, Chiara; Caironi, Mario
Abstract: Doped conjugated organic semiconductors are suitable materials to be used as building blocks of flexible and cost‐effective thermoelectric generators. While several efficient solution‐processable p‐type organic thermoelectric materials are reported, n‐doped materials are fewer because of lack of good electron‐transporting materials and stable n‐dopants. Here, n‐doping process is investigated on a relevant n‐type class, namely naphthalene‐diimide‐based copolymers. Among these, copolymer incorporating bithiophene (T2) donor units, largely studied poly N, N ″‐bis(2‐octyl‐dodecyl)‐1, 4, 5, 8‐naphthalenedicarboximide‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene) (PNDI‐T2), is one of first polymers reported to achieve good solution‐based n‐doping. By substituting T2 with thienylenevinylene‐thienylene (TVT), resulting PNDI‐TVT copolymer exhibits improvements on both structural and transport properties, offering a suitable basis to improve thermoelectric properties upon doping. When doped with 1 H ‐benzimidazoles, PNDI‐TVT achieves maximum in‐plane electrical conductivity at room temperature of 2.4 × 10 −2 S cm −1, being the highest value for PNDI‐T2 solution‐doped derivatives excluding those with oligoethylene‐glycol chains. Electron paramagnetic resonance and variable temperature electrical conductivity measurements relate this enhancement to more efficient charge‐transfer between n‐dopant molecules and host polymeric matrix, and easier charge carrier transport within the system. This electrical conductivity large enhancement also improves in‐plane power factor of almost three times with respect to similar doped PNDI‐T2 films. Abstract : Conjugated organic semiconductors are gaining the attention of the scientific community toward the development of flexible and cost‐effective organic thermoelectric generators. Here, the n‐doping process is investigated on naphthalene‐diimide‐based copolymers with thienylene‐vinylene‐thienylene donor units, achieving superior thermoelectric properties with respect to poly N, N ″‐bis(2‐octyl‐dodecyl)‐1, 4, 5, 8‐naphthalenedicarboximide‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene) parent moiety as doped with 1 H ‐benzimidazoles molecules with different N ‐alkyl substituents and structures.